Solid State Electronic Spectral Studies of Glycine-Halogen Charge Transfer Complexes - Baruah, S.K. (Asian Journal of Chemistry, 2012)
The electronic absorption studies have been made of the interaction between glycine and halogens (iodine, iodine-chloride and iodine-bromide) in solid states. It has been observed that glycine acts as a polar donor and probably ionizes the halogen molecule as (glycine)n + 2I2 === (glycinen I+) + I3– where n = 1, 2.... The bands at ca. 294 and ca. 363 nm give the evidence of the formation of triiodide negative ion in case of glycine-iodine interaction. Similarly for iodine-chloride and iodine-bromide complexes, evidences for the formation of ICl2– and IBr2– have also been observed. The formation constant (K) between glycine and iodine in methanol-water mixed solvent has been found to be 1.446 and 2.138. The K-values for ca. 292 and ca. 350 nm bands indicate the formation of 1 : 1 complexes. The free energy changes have been found to be -4.457 and -4.464 kcal/mol.